Governance and Institutions in the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2016)
To achieve a better future by 2040, most Filipinos express the need for simple and efficient government transactions, affordable government services, and the elimination of corruption. This paper expounds on that vision by explaining how effective public goods and services are hinged on a government and markets that are functioning well altogether. In assessing the current state of governance structure and institutions in the Philippines, this paper highlights issues and challenges that should be addressed in the next 25 years. It then presents several policy options and emphasizes the need for the progressive sequencing of implementation — from fixing current programs in order to create more jobs and further enhance human capital, to more ambitious and deeper structural reforms related to politics and elections, human development, economic competitiveness, and public finance and good governance innovations.